Effect of Insulin Plant (Costus igneus) Leaf Powder in Broiler Chickens (Gallus galluus domisticus) - Carla M Bagunoc; Amalia A. Royo; Risa M. Magalang (Universidade Estadual de Alagoas, 2023)
This experiment was conducted to evaluate the effects of insulin plant leaf powder in broiler chickens. One hundred (100) chicks of the same age and random sexes were purchased from the local agrivet supplier and were used in the study. There were five (5) treatments replicated four (4) times following the Completely Randomized Design (CRD) of the experiment. The treatments were as follows: Treatment A - basal diet with 5 grams of insulin plant leaf powder per kilogram of feeds, Treatment B- basal diet with 10 grams of insulin plants leaf power per kilogram of feeds, Treatment C- basal diet with 15 grams of insulin plant leaf powder per kilogram of feeds, Treatment D- positive control (antibiotics) and Treatment E- without insulin plant leaf powder (control). The result of study on basal diet of broilers with insulin plant leaf powder significantly affects the body weight, body weight gain, and feed consumption of broilers at 21 and 35 days of feeding. The broiler given insulin plant leaf powder on their basal diet lowers their feed consumption as the amount of insulin plant leaf powder increases. The dressing percentage of broilers given insulin plant leaf powder on their basal diet is slightly higher compared to those given with a plain basal diet. The broiler given insulin plant leaf powder on their basal diet gives higher income compared to the controls. The analysis of results revealed that insulin plant leaf powder had a significant effect on the growth performance of broilers varies on the amount added per kilogram of basal diet. The period of feeding the broilers with insulin plant leaf powder on their basal diet affects their health since it was observed that after 21 days of feeding, treated birds show signs of stress/sickness.